A Comparison of Economic Efficiency of Monoculture and Multiple Cropping Patterns: The Case of Cassava Farming in Ende, Indonesia - Lanamana, Willybrordus; Supardi, Philipus Nerius (Universitas Sebelas Maret, 2021)
Nuabosi cassava is an alternative carbohydrate source for the community, which is expected to be a substitute for rice. This commodity has the potential to be developed, but is limited in resources, so it requires technological breakthroughs. This study aims at analyzing the level of technical, allocative and economic efficiency between the cassava cropping pattern and the factors that affect the efficiency. The research was conducted in Randotonda Village, from November 2019 to January 2020 and the samples consisted of 61 monoculture farmers and 46 multiple cropping farmers. Data analysis was performed using the Cobb-Douglass stochastic frontier production function. The allocative and economic efficiency was examined with the stochastic frontier cost function approach. The results of stochastic frontier estimation show that all variables have a positive effect on the production variable. The variables having a positive effect on the total cost include the price of cassava cuttings, the price of fertilizer, production and the dummy cropping pattern. The average level of economic efficiency of monoculture farmers is lower than that of multiple cropping farmers. Factors that affect economic efficiency are age, length of time to cultivate, frequency of obtaining information, dummy of farmer group membership and dummy of cropping patterns. In short, the level of technical, allocative and economic efficiency of monoculture farmers is lower than that of multiple cropping farmers. Farmers are expected to pay attention to the types of plants that are suitable in implementing the multiple cropping pattern.